Urban Built-up Change Detection with Minimum Redundancy Maximum Relevance Approach - Thar Oo, Kyi; Myo Kyi, Khin; Cho, Zarli (International Journal of Computer Sciences and Engineering, 2020)
Urban built-up area information is required in various applications of land use planning and management. Urban environment is made up with the complex interactions with built up environment and the human communities living within the urban area. The aim of the system is to assess an effective building change detection system that can identify gains and losses of built-up areas in relation to other land cover of Multi-temporal satellite image of Mandalay city in Myanmar. The proposed system apply to combine with gray level histogram features with minimum redundancy maximum relevance (MRMR) approach for built-up change detection system. The experimental analysis revealed that the proposed system combination with histogram features based on MRMR which is more reliable in urban built-up change detection system.